EFEKTIVITAS PROGRAM SANITASI BERBASIS MASYARAKAT DALAM MENINGKATKAN DERAJAT KESEHATAN MASYARAKAT - Ani Saskia; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This research is motivated by the benefits of the establishment of the sanimas program facilities, namely improvements in terms of increasing the degree of public health, improving the quality of sanitation and environmental hygiene of the community. This study aims to describe the effectiveness of community-based sanitation programs in improving community health status in Korong Padang Manis Nagari Campago, V Koto Kampung Dalam Subdistrict, Padang Pariaman Regency. This type of research is qualitative using descriptive methods. The research was conducted in Korong Padang Manis, Nagari Campago, V Koto Kampung Dalam, Padang Pariaman Regency. Informants are determined by purposive sampling technique. The data used in this study are primary data and secondary data. The data was collected by means of interviews, observation and documentation study, with the validity test using source triangulation. Meanwhile, the data analysis technique is done by reducing data, presenting data, and drawing conclusions. The results showed that the effectiveness of the community-based sanitation program in improving the health status of the community in Korong Padang Manis was not yet effective. This is because the public's awareness is still low on maintaining the cleanliness of the environment for the infrastructure of the sanimas program and there are still people who throw garbage and defecate in the open